ECO-SPIRITUAL BASED ON MAQA>SID AL-SHARI>'AH: The New Relationship of Man with the Environment - Ibrahim Siregar; Suheri Sahputra Rangkuti (IAIN Ponorogo, 2023)
Theoretically, Islamic doctrines can adapt to the situation and conditions of reality. However, in Islamic history, it isn't easy to find studies about the importance of establishing a relationship with nature or the environment in which that reality stands. This research offers a paradigm that bridges the new relationship between humans and the environment. At this level, the author builds a paradigm with a multidisciplinary approach. Methodologically, maqa>sid al-shari>'ah is used as a paradigm foundation and umbrella for human actions when responding to their environment. This study found that the maqa>sid al-shari>'ah-based eco-spiritual paradigm is embodied in spiritual actions in the form of sacralization and ecological contemplativeness. Explicatively, sacralization and ecological contemplativeness are applied based on the principles of Islamic ethics, al-insija>m (harmony), al-iqtisa>d (equality), al-ta'a>nu>q (interdependency), and al-tanzi>f (cleaning).